Desafíos y perspectivas del Arbitraje Internacional: Reformas, Normativas y Nuevas Tecnologías - Vargas Soto, Sheilah (2025)
The present interview, conducted with the distinguished attorney Sheilah Vargas Soto, provides a rigorous and up-to-date analysis of the evolution of arbitration in Peru. Drawing on concrete examples, it examines the reasons that motivated the reform of the arbitration system and its impact on strengthening party autonomy and limiting judicial intervention. Likewise, it addresses key aspects of international arbitration, such as the application of the IBA Guidelines, the recognition of foreign awards under the New York Convention, and the role of umbrella clauses in disputes with investors, with reference to landmark cases such as Duke Energy and Kuntur Wasi. The discussion also reflects on the contribution of emerging technologies—such as artificial intelligence and cybersecurity—to arbitration practice, highlighting both their benefits and ethical warnings. A valuable contribution for understanding the evolution, complexity, and prospects of arbitration from a practical and specialized perspective.